Obtención de un extracto antociánico a partir del residuo de mora de castilla (rubus glaucus benth) (2019)
Andean blackberry is one fruit wide industrial interest and recognized for anthocyanins content. The solvents extraction of these components from blackberry byproduct was studied by extraction with ethanol, two method were used, soxhlet and ultrasound. The concentration was varied on 75%, 85% y 96% vol. It was identified that the extraction with ultrasound with 96% vol. ethanol, generated the highest yield of 65.85 5.25 g extract/100 g waste with 661.944 mg cyaniding-3-glucoside/L. The extract produced can be used as a natural dye considering that the presence of anthocyanins was verified by spectrophotometry and the qualitative color change test according to the pH.